Planning and Strategies for Learning Sentence Structure Arabic Language: a Systemic Literature Review - Ahmad Habin Sagala (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2023)
This research aims to determine the strategy for learning sentence structure Arabic language (tarkib) in Madrasah. The method used in this research is a qualitative approach with the type of library research, or a series of studies related to library data collection methods, or research whose research objects are explored through various library information in the form of books, encyclopedias, scientific journals, newspapers, magazines, and documents. In the discussion, several things are presented: the definition and purpose of sentence structure learning, methods, techniques, and how the sentence structure learning media itself. Several methods can be used to learn tarkib: the Qowa'id wa Tarjamah Method (grammar and translation), the question and answer method, and the drill method. The techniques of teaching tarkib are repetition, question and answer, making questions, changing tarkib, perfecting sentences, composing sentences, and matching exercises. The media that can be used are structure cubes, skid boards, and concept maps.